Determinants of clinician and patient to prescription of antimicrobials: Case of Mulanje, Southern Malawi - Morris Chalusa; Felix Khuluza; Chiwoza Bandawe (Public Library of Science (PLoS), 2022)
Background Antimicrobial resistance is an emerging problem in low- and middle-income countries. The problem is exacerbated by inappropriate prescription of antimicrobials. Factors that lead to overuse or inappropriate prescription of antimicrobials by the cadre of medical assistants, clinical technicians and clinical officers have received limited attention. This study investigated factors that influence prescription behaviours of antimicrobials among clinical officers in various health facilities in Mulanje district, Southern Malawi. Methods Qualitative study design exploring determinants of antimicrobial prescription from May to October, 2019, was used. In-depth interviews (n = 18) and focus group discussions (n = 2) were conducted with medical assistant (MA), clinical technicians and clinical officers (CO) from four health facilities in Mulanje district. COs are licensed medical practitioners with an initial three-year training and one-year internship while MAs are licensed medical practitioners with initial two-year training and one year internship. Purposive sampling was done to arrive at a sample size of 30 health cadres. Results Participants pointed out that patient preferences, beliefs and clinicians' inadequate education on this issue were among the factors that contribute to inappropriate antimicrobial prescription. 75% of clinicians showed lack of knowledge on the definition of antibiotic and antimicrobial resistance. Conclusion Inappropriate use of antimicrobials is facilitated by prescription decisions made by clinicians who are greatly influenced by their patients. Interventions aimed at improving antimicrobial prescription should target both clinicians and patients.